The Sportswashed Games : A Qualitative Analysis of the Responses to the 2022 FIFA World Cup Related Scrutiny - Lähteenmäki, Vennu (My University, 2024)
The 2022 Qatar World Cup has been one of the most recent and apparent examples of sportswashing. The thesis inspects the responses to the criticisms arising from the FIFA 2022 Qatar football World Cup. These criticisms are divided into three key categories. The first category addresses the corruption and bribery accusations towards FIFA and Qatar. The remaining two categories examine issues relating to Qatar’s treatment of migrant workers, and sexual minorities. The thesis analyses how mainly Qatari and FIFA officials have responded to the criticism concerning the issues of corruption, migrant workers’ rights, and sexual minorities’ rights. This is done qualitatively, analysing 24 separate interviews and statements, eight from each of the three categories. The responses are then analysed and categorised with the help of Image Repair Theory. Every interview or statement was found to have used one or two image repair strategies in their responses to the addressed issues. Most of the respondents used image repair strategies by attempting to reduce the offensiveness of the criticism they received, while evading responsibility from the criticism was also done frequently. The thesis concludes that Image Repair Theory is a useful instrument when analysing cases of sportswashing, although it has its challenges.
Keywords: sportswashing, Image Repair Theory, corruption, human rights